Targeting glycolysis in non-small cell lung cancer: Promises and challenges - Xu, Jia-Qi; Fu, Yan-Li; Zhang, Jing; Zhang, Kai-Yu; Ma, Jie; Tang, Jing-Yi; Zhang, Zhi-Wei; Zhou, Zhong-Yan (Frontiers in Pharmacology, 2022)
Metabolic disturbance, particularly glucose metabolism, is known as a hallmark of tumors including non-small cell lung cancer (NSCLC). Cancer cells tend to reprogram majority of glucose metabolism into glycolysis even under oxygen environment. Although glycolysis is not the efficient way of ATP production compared to oxidative phosphorylation, the inhibition of tumor glycolysis directly impedes cell survival and growth. This review focuses on the research advance of glycolysis in NSCLC and systematically provides an overview of the key enzymes, biomarkers, non-coding RNAs and signaling pathways that modulate the procedure of glycolysis and consequently tumor growth and metastasis in NSCLC. The current medications, therapeutic approaches and natural products which affect glycolysis in NSCLC are also summarized. We found that the identification of appropriate target and biomarker in glycolysis specifically for NSCLC treatment is still a challenge at present, although targeting LDHB, PDK1, MCT2, GLUT1 and PFKM might be promising targets in the treatment of NSCLC or its specific subtypes and Dppa4, NQO1, GAPDH/MT-CO1, PGC-1α, OTUB2, ISLR, Barx2, OTUB2 and RFP180 might be prognosis predictors of NSCLC. In addition, natural products may serve as a promising therapeutic approach targeting the multiple steps in glycolysis metabolism since natural products always present multi-target properties. The development of metabolism intervention targeting glycolysis with or without the combination of current therapy tends to be a potential therapeutic approach in NSCLC treatment. The aim of this review is to hint the research patten and interests on metabolic treatment of NSCLC.